Peptide substrate screening for the diagnosis of SARS-CoV-2 using fluorescence resonance energy transfer (FRET) assay - Alhadrami, Hani A. (Mikrochim Acta, 2021)
The novel corona (SARS-CoV-2) virus causes a global pandemic, which motivates researchers to develop reliable and effective methods for screening and detection of SARS-CoV-2. Though there are several methods available for the diagnosis of SARS-CoV-2 such as RT-PCR and ELSIA, nevertheless, these methods are time-consuming and may not apply at the point of care. In this study, we have developed a specific, sensitive, quantitative and fast detection method for SARS-CoV-2 by fluorescence resonance energy transfer (FRET) assay. The total extracellular protease proteolytic activity from the virus has been used as the biomarker. The specific peptide sequences from the library of 115 dipeptides were identified via changes in the fluorescence signal. The fluorogenic dipeptide substrates have the fluorophore and a quencher at the N- and the C- terminals, respectively. When the protease hydrolyzes the peptide bond between the two specific amino acids, it leads to a significant increase in the fluorescence signals. The specific fluorogenic peptide (H-d) produces a high fluorescence signal. A calibration plot was obtained from the changes in the fluorescence intensity against the different concentrations of the viral protease. The lowest limit of detection of this method was 9.7 ± 3 pfu/mL. The cross-reactivity of the SARS-CoV-2-specific peptide was tested against the MERS-CoV which does not affect the fluorescence signal. A significant change in the fluorescence signal with patient samples indicates that this FRET-based assay might be applied for the diagnosis of SARS-CoV-2 patients. [Figure: see text]